A novel electrochemical device for naringin quantification and removal from bitter variety of citrus fruits. (October 2021) - Gupta, Arun Kumar; Mishra, Poonam; Senapati, Mukut; Sahu, Partha Pratim
Abstract: Citrus fruits have been recognized as one of the most consumed fruits in terms of bioactive components but due to immediate bitterness (naringin bitterness) in its juice primarily affecting consumer seemliness. Here, a novel ion-exchange-based resistive sensor was fabricated using amberlite-IRA 400 Cl - on SiO2 /Si substrate as a sensing layer for both selective detection and removal of naringin from citrus juice. The fabricated device was calibrated with a standard naringin solution. The result presented the accuracy of 94.5%, 3 × 10 −4  mg/mL as lower limit of detection with a response time of 15–20s, findings were validated with HPLC also. Here, the Temkin sorption model was found to be suited to explain the naringin adsorption and the correlation coefficient (R 2 ) is estimated as 0.96, exhibiting high adsorption properties of the sensing layer. The debittering time of citrus fruit juice was optimized to be 60s showing a significant reduction in naringin compound with a minimum loss of bioactive compounds. The sensing layer of the device was used up to 8 cycles without significant performance deterioration, demonstrating its excellent reusability. The green route of naringin detection and bitterness removal in citrus fruit promises potential application in the fruit industry. Graphical abstract: Image 1 Highlights: A dual-purpose novel sensor was developed for the detection and removal of naringin from citrus juices. Response time, accuracy, and LLOD of the fabricated sensor were 15–20s, 94.5%, and 3 × 10 −4  mg mL −1 respectively. The fabricated device reduced bitterness upto 48% in 60 s only. Bitterness removal may be regulated and monitored as per the requirement using fabricated device. It can monitor the maturity of citrus fruit based on naringin content.